The piglet mycobiome during the weaning transition: a pilot study - Summers, Katie L (J Anim Sci, 2019)
The importance of the microbiota in the gastrointestinal tract of animals is recognized as a critical player in host health. Recently, the significance of the mycobiome has been recognized, but culture-independent studies are limited, especially in swine. Weaning is a time of stress, dietary changes, and a predisposition to infections, making it a time point of interest to industry. In this pilot study, we sought to assess and characterize the mycobiome in the feces of swine from birth through the critical weaning transition to investigate the mycobiome population and its temporal dynamics in piglet feces. Cultured fecal samples demonstrate a significant increase in fungal burden following weaning that does not differ from adult levels, suggesting stable colonization. Culturable fungi were not found in any environmental samples tested, including water, food, sow milk or colostrum. To determine the fungal diversity present and to address the problem of unculturable fungi, we performed a pilot study utilizing ITS and 16S rRNA focused primers for high-throughput sequencing of fungal and bacterial species, respectively. Bacterial populations increase in diversity over the experimental timeline (days 1 to 35 postbirth), but the fungal populations do not demonstrate the same temporal trend. Following weaning, there is a dynamic shift in the feces to a Saccharomycetaceae-dominated population. The shift in fungal population was because of the dominance of Kazachstania slooffiae, a poorly characterized colonizer of animal gastrointestinal tracts. This study provides insights into the early colonization and subsequent establishment of fungi during the weaning transition in piglets. Future studies will investigate the effect of the mycobiome on piglet growth and health during the weaning transition.